Path-designed 3D printing for topological optimized continuous carbon fibre reinforced composite structures. (1st February 2020) - Li, Nanya; Link, Guido; Wang, Ting; Ramopoulos, Vasileios; Neumaier, Dominik; Hofele, Julia; Walter, Mario; Jelonnek, John
Abstract: In current 3D printing technologies, it remains a great challenge to print continuous carbon fibre reinforced composites with complex shapes and high mechanical performances. The main reason lies in the limitation of printing path design, which cannot guarantee to print carbon fibres along load transmission paths of composite parts. Here we address this issue by proposing an ingenious path-designed 3D (PD-3D) printing approach that considers the load transmission path and anisotropic property of the continuous carbon fibre reinforced filament. Complex structures of carbon fibre reinforced composites, with enhanced lightweight, were demonstrated. Such structures of carbon fibres paving along load transmission paths, greatly reduce stress concentration and achieve a quasi-isotropic performance. By comparing printed specimens with drilled holes and semicircles, the PD-3D printed specimens with holes and semicircles are 67.5% and 62.4% higher in tensile and flexural strength, respectively. And the strength to weight ratio of the tensile and flexural specimens also increase by 55.1% and 35.2%, compared with the drilled ones.